2020
DOI: 10.3390/agronomy10121853
|View full text |Cite
|
Sign up to set email alerts
|

Differential Ozone Responses Identified among Key Rust-Susceptible Wheat Genotypes

Abstract: Increasing ambient ozone (O3) concentrations and resurgent rust diseases are two concomitant limiting factors to wheat production worldwide. Breeding resilient wheat cultivars bearing rust resistance and O3 tolerance while maintaining high yield is critical for global food security. This study aims at identifying ozone tolerance among key rust-susceptible wheat genotypes [Rust near-universal susceptible genotypes (RnUS)], as a first step towards achieving this goal. Tested RnUS included seven bread wheat genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Most of the tested genotypes (35 genotypes) are Egyptian wheat cultivars that consists of 27 old and new Egyptian cultivars that are planted regularly in the Egyptian fields in addition to eight breeding lines produced by Genetics Department, Faculty of Agriculture, Assuit University, Egypt. The tested genotypes included seven known rust susceptible checks (McNair701, Morocco, Rusty, LMPG-6, Thatcher, Line E, and Little Club; Mashaheet et al, 2020 ). The remaining 156 genotypes were evaluated under the Egyptian conditions and found to be adapted to these environmental conditions ( Mourad et al, 2020 ; Abou-Zeid and Mourad, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Most of the tested genotypes (35 genotypes) are Egyptian wheat cultivars that consists of 27 old and new Egyptian cultivars that are planted regularly in the Egyptian fields in addition to eight breeding lines produced by Genetics Department, Faculty of Agriculture, Assuit University, Egypt. The tested genotypes included seven known rust susceptible checks (McNair701, Morocco, Rusty, LMPG-6, Thatcher, Line E, and Little Club; Mashaheet et al, 2020 ). The remaining 156 genotypes were evaluated under the Egyptian conditions and found to be adapted to these environmental conditions ( Mourad et al, 2020 ; Abou-Zeid and Mourad, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Gerosa et al [ 33 ] found that two durum wheat cultivars (Virgilio and Neodur) that were exposed to a combination of high O 3 levels and saline irrigation in an OTC experiment showed no reduction in the main agronomic parameters when the plants were exposed only to increased O 3 levels. Nevertheless, other studies have identified O 3 -sensitive cultivars in relation to biomass growth and grain production [ 34 , 35 ], demonstrating that, similarly to T . aestivum , there is a remarkable variability in the O 3 -induced response within the Triticum genus depending on the species and cultivar considered [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This genotype was resistant to both blast and ozone. In a recent study targeting ozone tolerance and fungal resistance breeding, Mashaheet et al ( 2020 ) tested eight key rust-susceptible wheat genotypes for ozone tolerance and found differential responses. For example, bread wheat genotypes Thatcher and LMPG 6 showed severe sensitivity to ozone, whereas Chinese Spring showed tolerance for ozone-induced visible symptoms and biomass production.…”
Section: Discussionmentioning
confidence: 99%